Redefining Spirit Through the Body for the Healing and Flourishing of Trauma Survivors - Cargioli, Paige (Lumen et Vita, 2011)
Pastoral caregivers are mediators for healing both body and spirit. However, healing of the body through the spirit, and the spirit through the body is overlooked by caregiving disciplines. Different specialties emphasize more bodily healing or spiritual healing. For example, medical doctors and psychologists aim to heal bodies, while pastoral caregivers seek to heal the spirit. Additionally, this “healing” is complete once one reaches neutral functioning. I believe healing is, instead, a journey towards optimal functioning that is flourishing. In this paper, I explain how the body and spirit become disconnected in trauma survivors, and how those seeking healing ultimately are seeking to reconnect the body and spirit as one. That is to say, bodily trauma hurts the spirit, and vice versa. Secondly, I discuss the dangers of dualistic thinking and the language that separates body and spirit in society and among all types of caregivers, but especially pastoral caregivers. Finally, I connect how an integrative body/spirit approach leads to more holistic healing. Overall, I urge pastoral caregivers (as well as other disciplines) be more integrative, open-minded, and less dualistic in their approach to service and healing in order to build flourishing communities.